Economic Improvement and MSME Empowerment Through Digitalization of Marketing and The Concept of Syar'i Capital in Sontang Village: Peningkatan Ekonomi dan Pemberdayaan UMKMMelalui Digitalisasi Pemasaran dan Konsep Permodalan Syar’i di Desa Sontang - Hamsal, Hamsal; Hidayat, Hidayat; Samsudin , Dafrizal; Sukri, Al; Sundari, Eva; Hanafi, Imam (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Economic Improvement and MSME Empowerment through Marketing Digitalization and Syar'i Capital Concept in Sontang Village. Sontang village, known as the center of fishing activities and salai fish production, faces conventional marketing challenges and fuel constraints that are not in line with syar'i principles. This Community Service activity aims to improve the economy and empower MSMEs through marketing digitalization strategies and the application of the concept of syar'i capital. Participatory methods are used to actively involve communities in decision-making processes and identify common solutions. Through lectures, discussions, and business training, it is hoped that the people of Sontang Village can stimulate their creativity in developing the economy. Digital marketing strategies, including the use of mass media and business training, will increase product visibility and public knowledge about digitalization. The importance of the concept of syar'i capital is conveyed through counseling, with a focus on avoiding the MAGHRIB principle. The ultimate goal of this activity is the realization of market expansion and an increase in MSME income, along with a just economy in accordance with Islamic principles. With the hope that this approach will have a positive impact, this abstract summarizes efforts to improve the welfare of the people of Sontang Village through economic innovation based on Islamic values.